PENGARUH BUDAYA TERHADAP AKUNTANSI, AUDITING DAN PRAKTIK AKUNTANSI INTERNASIONAL - Priyastiwi Priyastiwi (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2016)
The purpose of this article is to provide the basic model of Hofstede and Grays’ cultural values that relates the Hofstede’s cultural dimensions and Gray‘s accounting value. This article reviews some studies that prove the model and develop the research in the future. There are some evidences that link the Hofstede’s cultural values studies with the auditor’s judgment and decisions by developing a framework that categorizes the auditor’s judgments and decisions are most likely influenced by cross-cultural differences. The categories include risk assessment, risk decisions and ethical judgments. Understanding the impact of cultural factors on the practice of accounting and financial disclosure is important to achieve the harmonization of international accounting. Deep understanding about how the local values may affect the accounting practices and their impacts on the financial disclosure are important to ensure the international comparability of financial reporting. Gray’s framework (1988) expects how the culture may affect accounting practices at the national level. One area of the future studies will examine the impact of cultural dimensions to the values of accounting, auditing and decision making.